Edoxaban Effects on Bleeding Following Punch Biopsy and Reversal by a 4-Factor Prothrombin Complex Concentrate. Issue 1 (6th January 2015) - Zahir, Hamim; Brown, Karen S.; Vandell, Alexander G.; Desai, Madhuri; Maa, Jen-Fue; Dishy, Victor; Lomeli, Barbara; Feussner, Annette; Feng, Wenqin; He, Ling; Grosso, Michael A.; Lanz, Hans J.; et al.
<x xml:space="preserve">Abstract</x> Background— The oral factor Xa inhibitor edoxaban has demonstrated safety and efficacy in stroke prevention in patients with atrial fibrillation and in the treatment and secondary prevention of venous thromboembolism. This study investigated the reversal of edoxaban's effects on bleeding measures and biomarkers by using a 4-factor prothrombin complex concentrate (4F-PCC). Methods and Results— This was a phase 1 study conducted at a single site. This was a double-blind, randomized, placebo-controlled, 2-way crossover study to determine the reversal effect of descending doses of 4F-PCC on bleeding duration and bleeding volume following edoxaban treatment. A total of 110 subjects (17 in part 1, 93 in part 2) were treated. Intravenous administration of 4F-PCC 50, 25, or 10 IU/kg following administration of edoxaban (60 mg) dose-dependently reversed edoxaban's effects on bleeding duration and endogenous thrombin potential, with complete reversal at 50 IU/kg. Effects on prothrombin time were partially reversed at 50 IU/kg. A similar trend was seen for bleeding volume. Conclusions— The 4F-PCC dose-dependently reversed the effects of edoxaban (60 mg), with complete reversal of bleeding duration and endogenous thrombin potential and partial reversal of prothrombin time following 50 IU/kg. Edoxaban alone and in combination with 4F-PCC was safe and well tolerated in these healthy subjects. A dose of 50 IU/kg 4F-PCC may be suitable for reversing edoxaban anticoagulation. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT02047565.